Nietzsche’s criticism of Kant’s moral duty - bdulelahyounus, hibaa (Journal of College of Education, 2021)
In spite of the great position that Kant’s philosophy carried in Nietzsche’s philosophy , especially the exceptional critical role of Kant and its effect on his dimension , since he awakened the mind to seek knowledge and challenges , including metaphysics from it ,the Kantian rational exalted in search of knowledge, truth, values and theorization of these compounds all this deems Nietzsche an exceptional and challenging matter Contrary to European civilization reality we see Nietzsche rejecting the principles of Kantian philosophy based on absolute rationality in its totalitarian buildings, including his theory of morality, which can be limited to a set of inevitable commandments governed by reason, and by which we must adhere and obey His attempt to make “duty” a logical act and just divine command s and moral values can be deduced only by reason and linking morality to the will emanating from the conscious human mind not from his desire and adherence to morality, and doing righteousness is a moral duty and respect for moral law is the motivation for moral action and because human knowledge is limited as he says ethics must To go beyond the narrow view that is limited to personal benefit, and quite the opposite, Nietzsche did not like Kant’s philosophy of morals and calls it moral intolerance, and it shows Kant’s religious instinct and his influence on Christian thought and his attempt to make “duty” a logical action and not just divine orders that l set among the Enlightenment thinkers Where we find that the reason for moral morality is rational, not religious, On the contrary, the philosophy of Nietzsche strives to destroy all values of morality on the basis of the necessity of liberating man from every belief or value, and because there no rule that can from the reference to any moral act and because in his opinion it is the other version of religion that He demanded his death What Kant did, in Nietzsche’s opinion, is the revival of religion with the philosophy of ethics, Therefore, Kant was not more than half a religious man and not a philosophy, With multiple minds, there are multiple moral values build his moral world by himself This is his imperative People perish if they sin and comply with the general duty instead of their own duty.